Solve for y 6*(-3y)=15

Math
6⋅(-3y)=15
Multiply -3 by 6.
-18⋅y=15
Divide each term by -18 and simplify.
Tap for more steps…
Divide each term in -18⋅y=15 by -18.
-18⋅y-18=15-18
Cancel the common factor of -18.
Tap for more steps…
Cancel the common factor.
-18⋅y-18=15-18
Divide y by 1.
y=15-18
y=15-18
Simplify 15-18.
Tap for more steps…
Cancel the common factor of 15 and -18.
Tap for more steps…
Factor 3 out of 15.
y=3(5)-18
Cancel the common factors.
Tap for more steps…
Factor 3 out of -18.
y=3⋅53⋅-6
Cancel the common factor.
y=3⋅53⋅-6
Rewrite the expression.
y=5-6
y=5-6
y=5-6
Move the negative in front of the fraction.
y=-56
y=-56
y=-56
The result can be shown in multiple forms.
Exact Form:
y=-56
Decimal Form:
y=-0.83‾
Solve for y 6*(-3y)=15

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top